The second sense : language, music, & hearing - Maconie, Robin (Scarecrow Press, 2002)
A vigorous non-technical discussion of basic acoustical, auditory, and communications processes that guide and connect musical behaviors of every age. Developed as a source book for students of art and design it offers illuminating commentaries on more than 100 cd recorded items from classical and world music traditions.